2010
DOI: 10.1074/jbc.m110.145698
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Role for let-7 MicroRNAS in Experimental Asthma

Abstract: MicroRNAs (miRNAs) are short, non-coding RNAs that target and silence protein coding genes through 3-UTR elements. Evidence increasingly assigns an immunosuppressive role for miRNAs in immunity, but relatively few miRNAs have been studied, and an overall understanding of the importance of these regulatory transcripts in complex in vivo systems is lacking.Here we have applied multiple technologies to globally analyze miRNA expression and function in allergic lung disease, an experimental model of asthma. Deep s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
193
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(213 citation statements)
references
References 59 publications
11
193
3
1
Order By: Relevance
“…Cultures were maintained in 5% CO 2 at 37°C. Bone marrow-derived mouse mast cells were isolated and cultured according to standard procedures (24). B16F1 and B16F10 melanoma cells were cultured in Dulbecco's modified minimal essential medium (DMEM; Gibco) supplemented with heat-inactivated 10% fetal bovine serum (FBS; Gibco) and antibiotics at 37°C in a humidified incubator with a mixture of 95% air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were maintained in 5% CO 2 at 37°C. Bone marrow-derived mouse mast cells were isolated and cultured according to standard procedures (24). B16F1 and B16F10 melanoma cells were cultured in Dulbecco's modified minimal essential medium (DMEM; Gibco) supplemented with heat-inactivated 10% fetal bovine serum (FBS; Gibco) and antibiotics at 37°C in a humidified incubator with a mixture of 95% air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition of miR-145 inhibits eosinophilic inflammation, mucus hypersecretion, T(H)2 cytokine production, and airway hyperresponsiveness (23). Let-7 miRNA mediates allergic lung disease by regulating the production of proinflammatory cytokines (24). Selective blockade of miR-126 suppresses the asthmatic phenotype, resulting in diminished T(H)2 responses, inflammation, airway hyperresponsiveness, eosinophil recruitment, and mucus hypersecretion (25).…”
mentioning
confidence: 99%
“…miR-375 was found to be down-regulated in IL-13 transgenic mice and repressed in human bronchial (and esophageal) epithelial cells by IL-13 (47). let-7 has a complicated but proinflammatory role in a murine model of asthma (48). Finally, broad-based miRNA profiling has been performed in murine models of acute and chronic asthma, identifying additional possible biomarkers (49).…”
Section: Airway Epithelial Micrornas As Endotypic Markersmentioning
confidence: 99%
“…miR-21 shows abnormal expression for vascular diseases in pulmonary [13]. It was revealed that miRNA-26 behaved as a regulatory factor in smooth muscle hypertrophy (enlargement) and let-7 miRNA increased the inflammatory related to asthma [14]. It is believed that miR-17-92 cluster (take part in 13q31.3) expressions of pulmonary to be high during embryonic development and low in adulthood, has a role in the regulation of pulmonary development [11,15].…”
Section: Discussionmentioning
confidence: 99%